A multicentre, cross-sectional study investigating the prevalence of hypertensive disease in patients presenting for elective surgery in the Western Cape, South Africa - Van Der Spuy, Karen (Department of Anaesthesia and Perioperative Medicine, 2019)
Background: Hypertension is common, affecting over one billion people worldwide. Importantly, in Sub-Saharan Africa hypertensive disease not only affects the older population group, but is becoming increasingly prevalent in younger patients. In South Africa, over 30% of the adult population has hypertension, making it the single most common cardiovascular risk factor and the predominant contributor to cardiovascular disease and mortality. In non-cardiac surgical patients, elevated blood pressure is the most common perioperative comorbidity encountered with an overall prevalence of 20-25%, and it remains poorly controlled in low and middle-income countries. Furthermore, hypertension in the perioperative setting may adversely affect patient outcome. It thus not only flags possible perioperative challenges to anaesthesiologists, but also identifies patients at risk of long-term morbidity and mortality. Objectives: The primary objective of this study was to determine the prevalence and severity of hypertension in elective adult surgical patients in the Western Cape. Results: The study population included all non-cardiac, non-obstetric, elective surgical patients from seven hospitals in the Western Cape during a one-week period. Hypertension, defined as having had a previous diagnosis of hypertension or meeting the blood pressure criteria of more than 140/90 mmHg, was identified in 51.8% of patients during the preoperative assessment. Significantly, newly diagnosed hypertension was present in 9.6% of all patients presenting for elective surgery. Although 98.1% of the known hypertensive patients were on antihypertensive therapy, 36.9% were inadequately controlled. Numerous reasons exist for this but notably 32% of patients admitted to forgetting to take their medication, making patient factors the most common cause for treatment non-compliance. Conclusion: This study suggests that the perioperative period may be an important opportunity to identify undiagnosed hypertensive patient. The perioperative encounter may have a significant public health implication in facilitating appropriate referral and treatment of hypertension to decrease long-term cardiovascular complications in South Africa.